Location Tracking of Moving Crew Members for Effective Damage Control in an Emergency - Kang, Hee Jin; Lee, Dongkon; Shin, Jong Gye; Park, Beom Jin (Defence Science Journal, 2010)
In an emergency, the commanding officer may have limited information, and crew members may behave differently compared to how they behaved during training. In an emergency situation, if the commanding officer is aware of each crew member's location and role in that situation, he can disseminate orders expeditiously and precisely. To realise a faster and more precise dissemination of orders through better awareness of each crew member's location and role, real-time crew member tracking is needed. The technical feasibility of a real time crew-tracking system based on a wireless sensor network has been studied, with the intent to improve effective commanding in an emergency. Herein, location tracking was achieved using instrumentation consisting of ZigBee tags, routers, and gateways, which were used to record the location and role data of moving crew members on a full-scale ship. Defence Science Journal, 2011, 61(1), pp.57-61, DOI:http://dx.doi.org/10.14429/dsj.61.503